The Contribution of Sri Lankan English Poetry to Sri Lankan Life - Shriganeshan, K. (The British Council, 2001)
This paper looks into the problems of Sri Lankan English poets who made a significant contribution in Sri Lankan English poetry. There have been tensions and differences of opinion among critics and linguists on the use of language, idiom, imagery and the themes used by the writers. Having considered some work by important poets like Kamala Wijeratne, Lakdasa Wikkramasinha, Anne Ranasinghe, Jean Arasanayagam, Suresh Canagarajah, Patrick Fernando and Richard de Zoysa and criticism by DCRA Goonetilleke, Rajiva Wijesinha, Thiru Kandiah, Suresh Canagarajah, Neloufer de Mel, Arjuna Parakrama, Kamal de Abrew, Ruvani Ranasinghe and Wilfred Jayasuriya, the study analyses the goals of Sri Lankan writers in English. Critics have spoken of an innovative idiom to express Sri Lankan experience in English but intelligibility is the other problem faced by international readers. The study focuses on the possibility of evolving a new idiom to express Sri Lankan life in English.